Pertanggung-jawaban Hukum atas Keputusan Otomatis Berbasis Kecerdasan Buatan: Studi Komparatif antara Uni Eropa dan Asia Tenggara - Nicholle, Melanie (Universitas Sains dan Teknologi Komputer, 2025)
This study analyzes legal accountability for automated decision-making based on Artificial Intelligence (AI) through a comparative study between the European Union (EU) and Southeast Asia. The research is motivated by the emergence of the EU AI Act, which establishes a binding risk-based legal framework, while ASEAN remains focused on non-binding ethical guidelines. Employing a qualitative–comparative approach, this study examines three key legal dimensions liability, transparency, and enforcement through a review of policy documents, regulations, and contemporary academic literature. The research gap lies in the absence of a conceptual model capable of bridging the EU’s hard law approach with ASEAN’s soft law framework in regulating automated decisions. The findings reveal a significant regulatory disparity between the EU and ASEAN, particularly in accountability, transparency, and enforcement mechanisms. While the EU prioritizes legal certainty and individual rights protection, ASEAN emphasizes flexibility and policy collaboration. This study proposes an adaptive “AI Accountability Framework” that integrates global ethical standards with regional legal norms to enhance ASEAN’s regulatory capacity. The findings contribute theoretically to the scholarship on technology law and practically to the formulation of AI governance policies that are fair, transparent, and accountable.